POLISH - UKRAINIAN COOPERATION OF LOCAL GOVERNMENT UNITS - Jaszczuk, Paulina (Review of European and Comparative Law, 2020)
Cooperation between neighboring countries, Polish and Ukraine has a rich history. If you want to talk about the cooperation of local government units between the two countries you must also make a comparison of the legal systems of both countries in this field. The aim of the article is therefore the analysis of the legislation governing the functioning of local government units in the crossborder cooperation and also attempt to compare them and draw conclusions and assessment of cooperation between local Polish and Ukrainian .